Benign Fibrous Histiocytoma of the Conjunctiva - Geoffrey Ryan; Bill Glasson; Andrew Foster (Case Reports in Ophthalmological Medicine)
A case is reported on recurrence of a rare conjunctival fibrous histiocytoma (FH) in a 38-year-old man. The lesion was excised and subsequently sent for histopathology and immunostaining resulting in a diagnosis of fibrous histiocytoma (FH). Recurrence was detected 3 months postoperatively requiring a conjunctivosclerokeratomy with cryotherapy and flap. At 6-month followup there was no recurrence detected.